2014
DOI: 10.1097/tp.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Circulating Endothelial Cells Count Could Become a Valuable Tool in the Diagnostic Definition of Acute Graft-Versus-Host Disease

Abstract: Changes in CEC count can represent a promising marker to monitor endothelial damage in patients undergoing allo-HSCT and could become a valuable tool in the diagnostic definition of GvHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
6
24
2
Order By: Relevance
“…20 Furthermore, the use of standardized criteria for signal intensity and automated image analysis guarantees a better reproducibility by reducing inter-operator variability. 20 As we previously reported, 19 we further confirmed, on a larger patient series, that statistically significant higher CEC counts (P o 0.003) are seen at engraftment in patients with no GvHD vs those who develop GvHD. This puzzling finding may also be correlated with the decreased CEC counts associated with higher GvHD grades we documented, although with the limitation of the low number of GvHD grade III patients and the lack of GvHD grade IV patients in our series.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…20 Furthermore, the use of standardized criteria for signal intensity and automated image analysis guarantees a better reproducibility by reducing inter-operator variability. 20 As we previously reported, 19 we further confirmed, on a larger patient series, that statistically significant higher CEC counts (P o 0.003) are seen at engraftment in patients with no GvHD vs those who develop GvHD. This puzzling finding may also be correlated with the decreased CEC counts associated with higher GvHD grades we documented, although with the limitation of the low number of GvHD grade III patients and the lack of GvHD grade IV patients in our series.…”
Section: Discussionsupporting
confidence: 75%
“…However, their encouraging findings need to be confirmed in larger studies to establish the real role of CEC as a biomarker of endothelial damage. 29 Not only does our study confirm a preliminary report 19 but it also represents the largest series of allo-HSCT patients where the clinical usefulness of CEC changes over time has prospectively been correlated to the diagnosis of GvHD and treatment response. Although CEC changes in allo-HSCT represent a dynamic phenomenon that can be influenced by many variables (among others, conditionings, immunosuppressive treatments, engraftment syndrome, infections), we clearly showed that CEC peaks were constantly seen prior to the onset of acute GvHD and invariably returned to pre-transplant values after treatment response.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Both of these strategies hold value in identifying HR patients, but neither take into account the endothelium, a key target of aGVHD associated with a poor prognosis. 6,[10][11][12] In addition, both of these strategies are based upon the extent of inflammation and tissue damage at presentation. Neither strategy considers the patient's capacity to heal damaged tissues, which recent data indicate may be a critical factor for response to therapy and potentially may explain discrepancies between assigned aGVHD risk and outcome.…”
Section: Introductionmentioning
confidence: 99%